Large‐Scale Synthesis of MOF‐Derived Superporous Carbon Aerogels with Extraordinary Adsorption Capacity for Organic Solvents. (17th December 2019) - Wang, Chaohai; Kim, Jeonghun; Tang, Jing; Na, Jongbeom; Kang, Yong‐Mook; Kim, Minjun; Lim, Hyunsoo; Bando, Yoshio; Li, Jiansheng; Yamauchi, Yusuke
Abstract: Carbon aerogels (CAs) with 3D interconnected networks hold promise for application in areas such as pollutant treatment, energy storage, and electrocatalysis. In spite of this, it remains challenging to synthesize high‐performance CAs on a large scale in a simple and sustainable manner. We report an eco‐friendly method for the scalable synthesis of ultralight and superporous CAs by using cheap and widely available agarose (AG) biomass as the carbon precursor. Zeolitic imidazolate framework‐8 (ZIF‐8) with high porosity is introduced into the AG aerogels to increase the specific surface area and enable heteroatom doping. After pyrolysis under inert atmosphere, the ZIF‐8/AG‐derived nitrogen‐doped CAs show a highly interconnected porous mazelike structure with a low density of 24 mg cm −3, a high specific surface area of 516 m 2 g −1, and a large pore volume of 0.58 cm −3 g −1 . The resulting CAs exhibit significant potential for application in the adsorption of organic pollutants. Abstract : Luftige Struktur : Kohlenstoffaerogele (CAs) auf MOF‐Basis wurden mit einer einfachen und nachhaltigen Strategie im Großmaßstab hergestellt. Die erhaltenen CAs haben eine poröse Struktur mit hoher Interkonnektivität, geringer Dichte (24 mg cm −3 ), großer spezifischer Oberfläche (516 m 2 g −1 ) sowie großem Porenvolumen (0.58 cm −3 g −1 ) und sind vielversprechend für die Anwendung bei der Adsorption organischer Verunreinigungen.